Innovation in Creative Writing Skills for Mathematics Textbooks Using the Design Thinking Method - Purbaningrum, Kus Andini; Saputra, Nisvu Nanda (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2024)
The need for learning tools that can be mastered by prospective teacher students in the School Field Experience Program (PLP) 2 requires fifth-semester students to develop the ability to design appropriate and effective learning materials. Mathematics textbooks are among the essential tools that must be created for PLP 2, making it necessary to guide students in writing textbooks through a dedicated course. This has led to an innovation in creative writing skills for mathematics textbooks using the design thinking method, which consists of five stages: empathize, define, ideate, prototype, and test. The results of this research include the physical development of school mathematics textbooks for middle and high school levels. Testing of the resulting products has placed them in the "very good" category, indicating their suitability for use as learning materials to support PLP 2 activities.